Impacts of neighborhood restaurant density on adults’ dietary quality: evidence from an IV-LASSO approach in China - Tang, Yalin; Zhu, Maoran; Zong, Jian; Zheng, Xuyuan; Liu, Chengfang (Frontiers in Sustainable Food Systems, 2025)
The development of the restaurant industry has disrupted food consumption patterns, while evidence on how restaurants impact dietary quality remains limited and inconsistent. This study is one of the first to demonstrate a non-linear, inverted U-shaped relationship between local restaurant density and dietary quality, leveraging data from four rounds of the China Health and Nutrition Survey (CHNS). To mitigate endogeneity issues, our analyses employ a LASSO-selected Instrumental Variable (IV) approach. Our results show that before reaching the threshold, the increase in neighborhood restaurant density, primarily driven by indoor restaurants, leads to improvements in residents’ dietary quality. However, once past the threshold, higher restaurant density reduces dietary quality, mainly driven by fast food restaurants. These effects are more pronounced among males with higher-income, and those living in urban and eastern China. The mechanisms underlying these relationships include the increased frequency of eating outside home (OH), with the similar inverted U-shaped relationship observed for dietary diversity further explaining our findings. We recommend supplementing neighborhoods with limited access to dining options through indoor restaurants, and mitigating the negative effects of excessive restaurants density, especially that of fast-food restaurants.